Application of Unpowered Automatic Fertigator for Aquaculture and Horticulture - Wulan Valenzya; Budi Indra Setiawan; Chusnul Arif (Jurnal Teknik Sipil dan Lingkungan, 2026)
The clean water crisis and the increasing scarcity of agricultural land pose significant challenges to food security. However, household yard areas, when managed productively, have the potential to contribute to family-level food production. The Powerless Automatic Fertigator (FONi) is an appropriate technology that has been shown to enhance productivity and facilitate various horticultural cultivation practices. This study integrates aquaculture and horticulture using the FONi system (referred to as FONi Mina-horticulture) with the following objectives: (1) to develop the system design and evaluate its performance; (2) to assess the production of fish and vegetables; and (3) to analyze land and water productivity. The experiment was conducted over a two-month period in a trial garden using a fish pond connected to 30 downstream planting pots. The water level in each pot was maintained at approximately 10 cm below the soil surface. Plant growth was measured weekly and monitored using CCTV. The results demonstrate that the FONi Minahorti model achieved a fish (grass carp) growth rate of 73% with a survival rate of 100%. Land and water productivity for red spinach were 7.67 g/m² and 8.77 g/L, respectively, while for green spinach they reached 10.08 g/m² and 11.53 g/L, respectively. The crop coefficient (Kc) for both spinach varieties during the growth period ranged from 0.40 to 0.71. These findings indicate that the FONi Minahorti system is a viable approach for enhancing yard productivity by simultaneously producing fish and vegetables to support daily household needs.